2017
DOI: 10.1002/cam4.1059
|View full text |Cite
|
Sign up to set email alerts
|

A large, single‐center, real‐world study of clinicopathological characteristics and treatment in advanced ALK‐positive non‐small‐cell lung cancer

Abstract: Crizotinib has achieved astonishing success in advanced non‐small‐cell lung cancer (NSCLC) patients harboring anaplastic lymphoma kinase (ALK) rearrangement. However, no real‐world studies described the clinicopathological characteristics and treatment of such patients in China. Patients were consecutively collected from Sun Yat‐sen University Cancer Center. Chi‐square test was applied to explore the relationship between ALK fusion status and metastasis sites. Kaplan–Meier methods and multivariable analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Our findings are consistent with the outcomes of previously published retrospective studies . It showed that the median PFS1 of crizotinib was 13.2 months, and the median TD of crizotinib among CBPD patients was 39.7 months.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with the outcomes of previously published retrospective studies . It showed that the median PFS1 of crizotinib was 13.2 months, and the median TD of crizotinib among CBPD patients was 39.7 months.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple‐covariate Cox regression analysis revealed that CBPD remained significantly associated with improved OS after adjusting for relevant factors. In real‐world studies, the reported median PFS of crizotinib treatment has ranged from 13.3 to 17.6 months . Liu et al reported that crizotinib continuation beyond the RECIST‐defined PD was feasible in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the PFS of patients receiving crizotinib as the initial therapy (median PFS, 18.5 months) was longer compared with the PFS results of the PROFILE 1014 (median PFS, 10.9 months) and PROFILE 1029 (median PFS, 11.1 months) trials. A similar PFS result (median PFS, 17.6 months) was reported in another real-world study from a single center in China (22). In the previous clinical trials (10,11), brain and bone scanning was repeated every 12 weeks to monitor for new lesions in the follow-up schedule.…”
Section: Discussionsupporting
confidence: 70%
“…Crizotinib, the first FDA‐approved ALKi for the treatment of advanced ALK‐positive NSCLC, has shown superior efficacy compared to the standard of care chemotherapy docetaxel and pemetrexed‐cisplatin doublet in the second‐ and first‐line setting, respectively . Disease progression usually occurs around 10 to 12 months during crizotinib treatment where the pattern of progression involves a high frequency of brain metastasis which targets the brain as a sanctuary site . This finding can be partly attributed to the drug transporters located at the blood brain barrier that actively efflux the therapeutic drugs and thereby reduce their concentrations in the brain tissue .…”
Section: Introductionmentioning
confidence: 99%